Urinary Tract and Gastrointestinal Infections during Pregnancy: Prevalence, Risk Factors, and Clinical Implications in a Pakistani Cohort - Sheema Khan, Sumreen, Farah Saleem, Brig. (R) Muhammad Farooq, Abdul Karim Soomro, Abdul Wadood Shah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Urinary tract infections (UTIs) and gastrointestinal (GI) infections are frequent complications of pregnancy and can adversely affect maternal and fetal health. In Pakistan, limited data address their combined prevalence, risk factors, and clinical impact. Objectives: To determine the prevalence, associated risk factors, pathogen distribution, and clinical outcomes of UTIs and GI infections among pregnant women. Methods: This descriptive cross-sectional study was conducted from March 2022 to May 2023 at the Gastroenterology Unit, Medical Teaching Institute/Khyber Teaching Hospital (MTI/KTH), Peshawar, and the Department of Obstetrics and Gynaecology, Dr. Faisal Masood Teaching Hospital, Sargodha. A total of 100 pregnant women aged 18–40 years were enrolled through non-probability consecutive sampling. Data on demographics, hygiene, dietary practices, and water source were obtained via structured interviews. Midstream urine and fresh stool samples were processed using standard culture, microscopy, and antigen detection. SPSS v26.0 was used for analysis, with Chi-square and logistic regression tests applied. Results: UTI prevalence was 28.0%, GI infection prevalence was 21.0%, and coinfection occurred in 5.0% of participants. UTIs were more common in the second trimester, while GI infections peaked in the third trimester. Poor personal hygiene was significantly associated with UTIs (p<0.001), and unsafe drinking water with GI infections (p<0.001). Escherichia coli was the predominant uropathogen, and Giardia lamblia the leading GI pathogen. UTIs were linked to preterm labor and low birth weight, while GI infections were associated with maternal dehydration and fetal growth restriction. Conclusion: These infections are common in pregnancy, largely preventable, and linked to adverse outcomes. Routine screening, hygiene promotion, safe water access, and dietary counseling are recommended to improve maternal and neonatal health. Keywords: Pregnancy, Urinary tract infection, Gastrointestinal infection, Risk factors, Pakistan.